2009
DOI: 10.1590/s0102-09352009000600023
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades da carne e perfil de ácidos graxos do pernil de catetos (Tayassu tajacu) alimentados com torta de babaçu (Orbignya phalerata)

Abstract: Propriedades da carne e perfil de ácidos graxos do pernil de catetos (Tayassu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Each installation contained a drinker and a feeder, providing the animals with free access to feed (Albuquerque et al, 2009). The climate was equatorial, with an average air temperature of between 24° and 27°C and an average annual rainfall greater than 2000 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Each installation contained a drinker and a feeder, providing the animals with free access to feed (Albuquerque et al, 2009). The climate was equatorial, with an average air temperature of between 24° and 27°C and an average annual rainfall greater than 2000 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The WRC of the palette (79.12%) and ham (78.49%) observed in this study were similar to that was reported by Fernandes et al (2015) for the fresh meat (79.10%) of collared peccary. Albuquerque et al (2009) analyzed the meat properties and fatty acid profile of the ham of collared peccaries fed with babassu (Orbignya phalerata) and found lower WRC values (59-63%). These authors related this result to the diet offer the collared peccary (with a high lipid content), that directly influenced the proximate composition of the meat of these animals.…”
Section: Physicochemical Analysis and Instrumental Colormentioning
confidence: 99%
“…Although very few data are available regarding the chemical composition of collared peccary, its meat has technological potential based on its noted levels of total proteins (21%) and low total lipids (1%), which are composed by oleic (28-37%), linoleic (13-22%), linolenic (0.2-0.6%) and palmitic (21-24%) acids (ω-6/ ω-3 = 37.9-60.0), as well as lower cholesterol levels (48.8%) than meats from other ruminants (Freire et al, 2000;Lopes et al, 2007;Saadoun & Cabrera, 2008). Ham meat from collared peccaries fed diets with different levels of babassu meal (Orbignya phalerata) have high content of unsaturated fatty acids, especially polyunsaturated (22-26%), which reduce cholesterol levels when added to human foods (Albuquerque et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This importance is related to the exploitation of the culture [34], which is extractive and exploited by lowincome people, as well as the substantial number of products and by-products that can be originated using this fruit. Babassu oil is the main product, usually used in the diet of the population of these regions [10,32,34] or for the production of cosmetics and hygiene and cleaning products [35,36], and, also for the production of biofuels [36 -38], being the byproducts destined for other uses, such as the use of the defatted cake for animal feed [34,39,40].…”
Section: Introductionmentioning
confidence: 99%